Composition of mango seed kernel - Augustin, M.A. (2013)
The seed kernels of 3 varieties of mango, Harumanis (MA 128), Siam Panjang (MA 205) and an unclassified variety grown in Malaysia were analysed. Proximate analysis showed that the seed kernels of these mango varieties contained 7.5-8.8% fat, 6.1-6.8% protein, 1.3-2.4% crude fibre and 2.2-2.8% ash. The amino acid profiles of mango seed kernel protein showed that the contents of most of the essential amino acids were higher than the FAO Reference Protein. The main component fatty acids of the mango kernel fat were palmitic (6.9-7.3%), stearic (44.3-44.4%), oleic (38.9-42.1%) and linoleic (4.5-7.4%) acids.